STEPS IN THE PROCESS OF POLITICIZATION AND BASIC TYPES OF POLITICS SUBJECTS - S. I. Nekrasov; N. A. Nekrasova; O. M. Khokhlowa (Научный вестник МГТУ ГА, 2016)
The article analyzes the main stages of personality’s politicization. The main types of political subject have been treated. Determined that agreement basically has everyone’s desire to be part of a group, team, company, and disagreement basically contains a human being’s desire to leave the team, to oppose it.